The Implications of Indonesia’s Shift in Palm Oil Exports from the European Union to China: a World-Systems Theory Analysis - alif dani herlambang; tubagus ari wibawa mukti; ida bagus putu aditya; indra krishnamurti (LIAISON JOURNAL OF BEST, 2023)
Abstract. For years Indonesia’s domestic economy has been relying on a strongly performing palm oil industry. Indonesia’s booming palm oil exports have, however, has been hampered by recent developments in the European Union, where policy-making, consumer preferences and other factors have led to the risk of a ban of Indonesian palm oil. Indonesia is projected to shift its exports to a new market – China. In this research, an analysis placed in the critical environment of the British School of International Political Economy (IPE) and the World-Systems Theory (WST), wishes to untangle politico-economic implications concerned with such shift. The research concludes that a critical analysis of an Indonesian shift of palm oil exports from the EU to China, will lead to the shifted Indonesian exposure to dependency, now, however, with potentially more threatening effects. Furthermore, the trade war between the United States and China acts as a catalyst to previously stated threatening effects – trapping Indonesia. The research recommends Indonesia to safeguard its own rights to avoid falling into a trap of devastating dependency Keywords: World System Theory, IPE, Trade War, Palm Oil